2020
DOI: 10.2337/db20-0382
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Omics Analyses Reveal Epigenetic Memory in Diabetic Renal Cells Regulating Genes Associated With Kidney Dysfunction

Abstract: Diabetic kidney disease (DKD) is a major complication of diabetes and the leading cause of end-stage renal failure. Epigenetics has been associated with metabolic memory in which prior periods of hyperglycemia enhance the future risk of developing DKD despite subsequent glycemic control. To understand the mechanistic role of such epigenetic memory in human DKD and to identify new therapeutic targets, we profiled gene expression, DNA methylation, and chromatin accessibility in kidney proximal tubule epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Systemic hypertension occurs frequently in diabetics and worsens intraglomerular hypertension and kidney microvascular damage. Bulk transcriptomic studies have been informative in both experimental models and human DKD (Bansal et al, 2020;Fan et al, 2019;Komers et al, 2014;Woroniecka et al, 2011). These studies have revealed important insights but are also limited because signals from minority cell types are lost in the integrated dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic hypertension occurs frequently in diabetics and worsens intraglomerular hypertension and kidney microvascular damage. Bulk transcriptomic studies have been informative in both experimental models and human DKD (Bansal et al, 2020;Fan et al, 2019;Komers et al, 2014;Woroniecka et al, 2011). These studies have revealed important insights but are also limited because signals from minority cell types are lost in the integrated dataset.…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by in vivo findings in diabetic mice prone to atherosclerosis ( 40 ), suggesting that SET7 could be a useful therapeutic target. Recently, we performed multiomics analyses of renal tubular cells from subjects with T2D versus control subjects, which revealed epigenetic memory of dysregulation of several key genes associated with DKD and renal function ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Roles of epigenetic modifications are not fully elucidated. Recently, single nucleus ATCT-seq integrated with snRNA-seq has been used to detect the cell-type-specific chromatin accessibility which enable to deep understanding of cell heterogeneity in kidney ( Bansal et al, 2020 ; Muto et al, 2021 ). It may provide a new approach to understand the epigentic modifications in DN.…”
Section: Discussionmentioning
confidence: 99%